(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Objectives: To determine the necessity of ureteral stenting after uncomplicated ureteroscopic lithotripsy for distal ureteral calculi (≤15mm). Materials & Methods: This prospective comparative study was conducted in the Department of Urology at Dhaka Medical College, Dhaka from July 2016 to June 2018. Study population included the patients aged 18 to 60 years whoattended in the outpatient Department of Urology, Dhaka Medical College Hospital, Dhaka with distal ureteric stone (≤15mm). After admission patients were studied clinically andwas selected for treatment and study purpose as per selection criteria. A total of 60 patients included with distal ureteric stone underwent uncomplicated ureteroscopic lithotripsy using a pneumatic device without ureteral dilatation. They were randomized equally into non-stented Group-A (n=30) and stented Group-B (n=30). All the cases were evaluated by history taken and relevant investigations were done. Each patient was followed up and evaluated at immediate(day 1-3), after 2 weeks (1st visit) and after 90 days (2nd visit) postoperatively. Test statistics were used to analyze the data are Chi-square Test, Student "t" test (unpaired) and Fisher’s exact probability test. P<0.05 was considered as significant. Result: Considering age, gender and stone size there was no significant difference in between two groups. Stone clearance was 100% in both groups. Mean operative time was much higher in group B (stented) patients as compared to that of group A patients. It was statistically significant (P<0.05). Mean hospital stay was 1.42 (±36) days in group A and 2.38 (+54) days in group B (stented). It was statistically significant (p<0.05). Difference between group A and B in immediate postoperative evaluation was significant (p<0.05). That means group A was better than group B. Comparative evaluation after 2 weeks (1st visit) shows some differences (higher in Group-B). Irritative bladder symptoms were staggeringly less frequent in Group-A. In between two groups, medical revisit and urinary tract infection were not different statistically. Evaluation of study groups after 90 days (2nd visit) none of both groups had ureteral stricture or stone fragments residue. Other outcome variables included were also insignificant and commonly less in group A, statistically insignificant (p>0.05). Conclusion: This present study revealed that non-stented uncomplicated ureteroscopy is a safe and effective procedure and also a better option for the management of distal ureteric stone (≤15mm) using rigid ureteroscope in terms of less complication, less operative time and cost effective.So, ureteral stenting following uncomplicated ureteroscopic lithotripsy for distal ureteral stone (≤15 mm) may be avoided or selectively used instead of routinely used. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 17-22